Governance and decentralized energy transitions: a comparative case study of three medium-sized cities in Sweden, Canada, and the United States. - Martin Boucher (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This study examines the impact of governance on decentralized energy transitions. Knowledge of how particular jurisdictions and their governance arrangements influence these transitions can help strengthen and contextualize divergent trajectories of decentralized energy transitions and-most importantly-reveal the role of geographical context in policy change.~Design: This research gap is addressed in this paper by comparing the uptake of decentralized energy transitions in three cities in three different countries-Lulea (Sweden), Saskatoon (Canada), and Anchorage (United States). The jurisdictions in each city has unique governance contexts pertaining to electric utilities, regulations, public policy, and public acceptance. ~By comparing these transitions, this study highlights the governance considerations for decentralized energy transitions and asks how does governance impact decentralized energy transitions in cities? To answer this question, actors within various public, private, and sectoral capacities were interviewed to provide their insights on decentralized energy transitions in each jurisdiction.~Conclusion: I present five governance dimensions that impact decentralized energy transitions and explain how these factors can be included to provide a more contextual understanding of patterns of decentralized energy transitions in cities. ~Originality: Much of the literature on decentralized energy and cities has focused on project and sectoral level analysis and hasn't considered the holistic nature of the energy system transition. A particular gap that would help inform a broader understanding is the jurisdictional governance impacts of decentralization energy transitions.~Implications of the Research: In practical terms, the results could be used to inform inter-jurisdictional comparisons of decentralization energy projects.~Limitations of the Research: Given that there were three case studies, it is not possible to make generalizable claims from the results.
Keywords: 330; Sustainability transitions; comparative method; urban energy systems; decentralized energy; governance challenges; and energy transitions